A Review on the effects of PVD RF sputtering parameters on rare earth oxide thin films and their applications. Issue 1 (July 2021) - Mandal, Pramod; Singh, Udai P.; Roy, Sudesna
Abstract: This article provides a review on effect of processing parameters on the quality and performance of thin films of rare earth materials deposited through PVD RF sputtering technique. The applications of these thin films include optical, electronics, medical films, defence and renewable energy technologies. A systematic review of the literature revealed that the sputtering parameters such as plasma power and substrate temperature have the most impact on the grain size of the deposited thin films. Larger grain size was observed to be at higher sputtering power and higher substrate temperatures, while lower grain size was obtained when the sputtering power is decreased. The optical property, in particular the band energy gap (Eg ) was found to improve with the film thickness. Thin films produced at higher doping concentration and subsequently annealed at higher temperature was found to increase the crystallinity of thin films.